Suitable and Available Land for Settlement Development in Cianjur Regency - Nurul Amaliyah Tanjung; Rustiadi Ernan; Widiatmaka (Graduate School Bogor Agricultural University (SPs IPB), 2021)
A merging of Jakarta and Bandung metropolitans influence the development of the areas around them. Consequently, people are migrating to the cities caused an increasing population. It leads to experiencing uncontrolled advancement and arising problems. One of them is the raising land demand for settlement development, but the land is limited. Therefore, there is a need to address these particularities. This research aimed to model suitable and available land for settlement development in Cianjur Regency. Multi-criteria evaluation (MCE) and geographical information system (GIS) were collaborated to define the suitability criteria. The analytical hierarchy process (AHP) was employed to set the criteria's weight. Spatial Plan and LP2B were carried out as limiting factors. The result showed that the most crucial consideration came from the disaster. The suitability classes in Cianjur regency are: highly suitable 36%, Suitable 7%, Marginally suitable 44%, and Not suitable 14%. 85% of land in 2018 was available for settlement. Yet it is decreasing becomes 2% in 2030. Therefore, the potential land for settlement development is The different perspectives among developers, academics, and government in determining the most critical criteria for land suitability plays a crucial role in the next Cianjur’s settlement development planning. The implementation of the Spatial Plan can minimize environmental problems such as land conversion. In addition, regarding the new regulation on LP2B, the Spatial Plan has to be updated to synchronize the plan between Spatial Plan and LP2B.